Crowd Control Analysis in Organizing The 2024 Religious Celebration Festival: A Qualitative Approach - Allana Leonardus; Ayu Asriyani; Hilary Quenella Moeis; Mirza Balqis Salwa Salmira; Jessica Ignatia Tambunan (TOBA: Journal of Tourism, Hospitality, and Destination, 2024)
One of the largest religious celebration festivals in Indonesia, attracting tens of thousands of visitors both domestically and internationally, involves complex event management. Therefore, the event is required to have a comprehensive risk management strategy to ensure safety, security, and smooth operation. This research aims to examine and analyze crowd control during the religious celebration festival in 2024. The method used by the researchers is a qualitative approach, collecting data through in-depth interviews and participatory observation. The data processed comes from sources who are event organizers involved in crowd management. Furthermore, data analysis is conducted using thematic analysis methods to identify risk categories and the mitigation strategies applied. This research shows that the highest level of risk at the religious celebration festival is crowd control. Therefore, the mitigation policies implemented by the event organizers include contingency planning, training and simulations for security personnel, backup plans for weather changes, and collaboration with various related parties. It is hoped that this research can provide insights for religious event organizers in managing and facing risks in similar events in the future